Penerapan Agile Development Methodology dalam Sistem Penjualan Buku dengan Fitur Kategori dan Pencarian - Aldisa, Rima Tamara; Abdullah, Mohammad Aldinugroho (Forum Kerjasama Pendidikan Tinggi, 2022)
In the current digital era, it is very important that business people need a website to make it easier to make sales online, buyers can search for goods without having to come to the store. Books are windows of knowledge. The Bookstore sells various types of best-selling book categories, latest books, school textbooks, cooking books, internet computer books, internet computer books, comics and novels, religious books, self-development books. The problem is that the bookstore owner has difficulty in knowing sales reports, difficulties in the number of available or empty book stocks, types or categories of books that cannot be separated. Designing a book sales information system and software developed using the Agile Development Methodology. The purpose of this study is that bookstores can have a website that attracts buyers, is easy to use and access, has a book category and search for books to make it easier for buyers to find the books they want and also make it easier for owners to manage book stock and reports